Everyday practices research: the analysis of religious travel practices in Belarusian society - Shkurova, Elena V.; Burak, Tatsiana V. (Journal of the Belarusian State University. Sociology, 2021)
The article discusses the importance of travel practices in the structure of social relations between religious subjects in the field of involvement in interfaith relations. The results of a sociological study of travels to holy places are presented in a combination of quantitative and qualitative methodology, questionnaire survey and semiotic analysis of texts. A qualitative approach to the study of religiosity provides an in-depth interpretation of the religious practices pecularities. However, the quantitative representation is relevant to identify general trends in the formation of strategies of religious behaviour. The model combinatig qualitative and quantitative methods of studying tourist practices provides the possibility of their complex analysis. The experience of carried out sociological research shows how qualitative research data can clearly complement the structural characteristics of religious travel (quantitative indicators) with the features of the subjectivity of such travel. The study found: 1) a religious journey involves the implementation of everyday practices of reproduction of meanings and participation in intercultural interaction, as well as the implementation of sacred rituals; 2) a notable number of the religious population in Belarus has experience of religious travel, but pilgrimage is not a regular practice for a significant part of them; 3) the iconic pilgrimage structure is constructed in the virtual verbal texts of Belarusians involved in the daily practice of travelling to holy places. It is formed by several components of the meaning of the «path»: life, the spiritual path, search, cognition, communication, unity, collective emotions.
Keywords: religious travel; everyday practice; cross-confessional model of religiosity; representations of pilgrimage experiences; pilgrimage